Optical Medium Approach: Simplifying General Relativity and Nonlinear Electrodynamics for Educational Purposes - Saken Toktarbay; Nurzada Beissen; Manas Khassanov; Temirbolat Aitassov; Amina Sadu (Physics)
This paper explores the optical approach to simplifying complex concepts in general relativity (GR) and nonlinear vacuum electrodynamics. The focus is on using optical analogies to simplify the understanding of spacetime curvature and interactions in strong gravitational and magnetic fields. We demonstrate how applying concepts of effective refractive index can facilitate the teaching and comprehension of GR optical effects, such as gravitational lensing and the behavior of light around massive objects. Additionally, the paper covers the application of optical analogies in the context of nonlinear vacuum electrodynamics, showing how strong magnetic fields affect light propagation. This interdisciplinary approach provides a more natural understanding and modeling of complex physical phenomena, making them better accessible for study and teaching.